2008
DOI: 10.1097/tp.0b013e31816632ed
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Airway Obliteration by Ciprofloxacin in Experimental Posttransplant Bronchiolitis Obliterans

Abstract: Ciprofloxacin attenuates airway rejection after tracheal transplantation. Genetic expression of mediators that are known to play an important role in mediating rejection in this model supports an immunomodulatory and antifibrotic role of ciprofloxacin. These findings suggest that further clinical studies are needed to investigate whether ciprofloxacin in addition to its bactericidal effect might be beneficial in the treatment of human posttransplant bronchiolitis obliterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Remund K et al has shown that ciprofloxacin attenuates airway obliteration after tracheal transplantation and that this effect may be based on the modulation of the TH1/TH2-balance by this antibiotic drug. 20 As already described imbalance in the TH1/TH2 parameters play a role in the development of IBD. This may be another mechanism by which ciprofloxacin has shown antiinflammatory activity in the present study.…”
Section: Figure 1 (C): Histopathological Evaluationmentioning
confidence: 89%
“…Remund K et al has shown that ciprofloxacin attenuates airway obliteration after tracheal transplantation and that this effect may be based on the modulation of the TH1/TH2-balance by this antibiotic drug. 20 As already described imbalance in the TH1/TH2 parameters play a role in the development of IBD. This may be another mechanism by which ciprofloxacin has shown antiinflammatory activity in the present study.…”
Section: Figure 1 (C): Histopathological Evaluationmentioning
confidence: 89%
“…Heterotopic tracheal transplantation was performed as previously described [14,15]. In short, donor tracheas were explanted, cut into halves, and implanted subcutaneously into the neck of recipient animals.…”
Section: Heterotopic Tracheal Transplantation and Experimental Groupsmentioning
confidence: 99%
“…Histologic slides were analyzed in a blinded fashion by computerized morphometry using Adobe Photoshop CS3 software (Adobe, San Jose, USA). The relative extent of tracheal obliteration, epithelial coverage and exposure of the basal membrane was calculated as described before [15].…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations